2016
DOI: 10.1109/tsmc.2015.2468678
|View full text |Cite
|
Sign up to set email alerts
|

A New Dexterous Hand Based on Bio-Inspired Finger Design for Inside-Hand Manipulation

Abstract: This paper presents a new design of finger proposed by the ROBIOSS team of the PPRIME Institute: it is a fully actuated bio-inspired four-degree-of-freedom (DOF) finger driven by four actuators. It has been developed with the aim to replicate fine manipulation with fingertips with a high degree of interaction with the environment. This paper proposes to realize a robotic hand for inside-hand fine manipulation and adaptive grasping. The robotic hand is equipped with fingers whose design is based on a human anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…While the former group mainly contains optimized grasp algorithm testing platforms, the latter consists of more versatile devices. As proof of the above statement concerning the number of fingers, Lee et al [90] and Mnyusiwalla et al [89] present robotic hands that perform in-hand manipulation of a ruler, bulb, and can. 3 clearly shows no dependencies or a trend of an increasing number of constructions with fewer than five fingers, and the ratio of these mechanisms is dropping.…”
Section: Finger Configurationsmentioning
confidence: 90%
See 2 more Smart Citations
“…While the former group mainly contains optimized grasp algorithm testing platforms, the latter consists of more versatile devices. As proof of the above statement concerning the number of fingers, Lee et al [90] and Mnyusiwalla et al [89] present robotic hands that perform in-hand manipulation of a ruler, bulb, and can. 3 clearly shows no dependencies or a trend of an increasing number of constructions with fewer than five fingers, and the ratio of these mechanisms is dropping.…”
Section: Finger Configurationsmentioning
confidence: 90%
“…Most artificial hands are human-based, which means that there are four palm fingers (index-little) and a thumb [38,[70][71][72][73]. However, some research groups found solutions with three [74][75][76][77][78][79][80][81] or four [23,40,[82][83][84][85][86][87][88][89][90] fingers applied ( Figure 3). While the former group mainly contains optimized grasp algorithm testing platforms, the latter consists of more versatile devices.…”
Section: Finger Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bio-inspired robotic hand project [39,40] is a complex mechatronic system. Starting from requirements, through use cases, mechanical and electrical architecture design, up to control algorithm functions, they all can be embedded within the MagicGrid process.…”
Section: Mbse In Practicementioning
confidence: 99%
“…The methods proposed in this subsection can improve the quality and efficiency of mechatronic and cyber-physical systems design processes. Regardless of the problem's complexity (new dexterous robotic hand [39,40], experimental reactor [41], extrusion-based additive manufacturing machine [42], satellite [20,24,25], loader crane [105], 5-axis milling machine [61]), the following workflow can be applied:…”
Section: Generic Workflow For Model-based Designmentioning
confidence: 99%